2018
DOI: 10.3892/or.2018.6936
|View full text |Cite
|
Sign up to set email alerts
|

miR‑107‑5p promotes tumor proliferation and invasion by targeting estrogen receptor‑α in endometrial carcinoma

Abstract: The aberrant expression of miR107-5p is closely related to the development of several types of human cancers. However, the role of miR-107-5p in endometrial carcinoma (EC) has not been fully confirmed. In the present study, we aimed to explore the function of miR-107-5p in EC carcinogenesis. EC samples and normal endometrial tissues were obtained by laser capture microdissection. It was determined that the expression of miR-107-5p in EC was significantly higher than that in normal endometrium, and higher miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
(39 reference statements)
0
28
0
Order By: Relevance
“…293T cells (5x10 4 /well) were seeded into 24-well plates and transfected with 0.2 µg of either pGL3-ESR1/AR-3'UTR-WT or pGL3-ESR1/AR-3'UTR-MT. The luciferase reporter assay was performed as previously described ( 16 , 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…293T cells (5x10 4 /well) were seeded into 24-well plates and transfected with 0.2 µg of either pGL3-ESR1/AR-3'UTR-WT or pGL3-ESR1/AR-3'UTR-MT. The luciferase reporter assay was performed as previously described ( 16 , 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The aberrant expression of miRNAs has been reported in various tumors ( 12 ), such as endometrial cancer ( 13 ), ovarian cancer ( 14 ), and CC ( 15 ). Our previous study demonstrated that miR-107-5p could promote tumor proliferation and invasion by targeting ERα in endometrial carcinoma ( 16 ); therefore, it was hypothesized that specific miRNAs may control ERα and AR expression post-transcriptionally during CC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 5 years, up to 754 miRNAs [ 17 ] have been identified as potential biomarkers in EC, some of which are correlated with lymph node involvement, advanced FIGO stage, metastatic status, or histologic type [ 17 , 40 , 103 , 118 , 161 , 162 ]. Increasing our knowledge of the miRNA expression status or the methylation state of key miRNA loci may help to better stratify patients.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, miR-203 suppresses the estrogen-induced viability, migration and invasion of ERα-positive breast cancer cells [68]. miR-107-5p has a direct interaction with ESR1 to enhance the proliferation and invasion of endometrial carcinomas [69]. On the other hand, miR-195 suppresses epithelial-mesenchymal transition by targeting G protein-coupled ESR1 in endometrial carcinomas [70].…”
Section: Mirnas and Er Function In Cancersmentioning
confidence: 99%